Association between thyroid hormones and diabetic kidney disease in euthyroid type 2 diabetes mellitus patients - Liu, Jun; Jiang, Wenwen; Liang, Jingjing; Ye, Xiaozhen; Yang, Xinyi; Wang, Qi; Chen, Min; Meng, Hanlu; Shen, Qiuyue; Zhong, Yong; Shao, Jiaqing (Frontiers in Endocrinology, 2026)
BackgroundThyroid hormones play an important role in the growth and development of the kidneys. However, there are few reports focusing on the correlation between thyroid hormones and diabetic kidney disease (DKD). The purpose of this study was to explore the association between thyroid hormone levels and DKD in euthyroid patients with type 2 diabetes mellitus(T2DM).MethodsWe conducted a retrospective cross-sectional study among hospitalized T2DM patients, and a total of 559 patients were enrolled in this study. The patients were divided into two groups: 136 in the DKD group and 423 in the non-DKD group. All patients received continuous glucose monitoring (CGM), and glucose variability indices were recorded, including the standard deviation of glucose levels (SD), coefficient of variation of glucose (CV), mean amplitude of glycemic excursions (MAGE), and mean of daily differences in glucose (MODD). Univariate ANOVA, Pearson/Spearman correlation analysis, and multivariate logistic regression analysis were employed to investigate the relationship between thyroid hormones, glucose variability, and DKD.ResultsThe DKD group exhibited lower free triiodothyronine (FT3) levels compared to the non-DKD group. In patients with type 2 diabetes, glycemic variability indicators (SD, CV, MODD) showed a significant decreasing trend across FT3 tertiles. Furthermore, FT3 was negatively correlated with SD, CV, and MODD. Multivariate logistic regression analysis revealed that FT3 and thyroid-stimulating hormone (TSH) were related to the presence of DKD.ConclusionsIn euthyroid patients with T2DM, thyroid hormone levels influence glycemic variability. Lower levels of FT3 within the normal range are associated with greater glycemic fluctuations. Additionally, in these patients, FT3 and TSH levels are correlated with the occurrence of DKD. Reduced FT3 levels and elevated TSH levels worked as risk factors for the prevalence of DKD.